Human thrombin-derived host defense peptides inhibit neutrophil recruitment and tissue injury in severe acute pancreatitis - Merza, Mohammed (2015)
Severe acute pancreatitis (AP) is characterized by leukocyte infiltration and tissue injury. Herein, we wanted to examine the potential effects of thrombin-derived host defense peptides (TDPs) in severe AP. Pancreatitis was provoked by infusion of taurocholate into the pancreatic duct or by intraperitoneal administration of L-arginine in C57BL/6 mice. Animals were treated with the TDPs GKY20 and GKY25 or a control peptide WFF25 30 min before induction of AP. TDPs reduced blood amylase levels, neutrophil infiltration, hemorrhage, necrosis, and edema formation in the inflamed pancreas. Treatment with TDPs markedly attenuated the taurocholate-induced increase in plasma levels of CXCL2 and interleukin-6. Moreover, administration of TDPs decreased histone 3, histone 4, and myeloperoxidase levels in the pancreas in response to taurocholate challenge. Interestingly, administration of TDPs abolished neutrophil expression of Mac-1 in mice with pancreatitis. In addition, TDPs inhibited CXCL2-induced chemotaxis of isolated neutrophils in vitro. Fluorescent-labeled TDP was found to directly bind to isolated neutrophils. Finally, a beneficial effect of TDPs was confirmed in L-arginine-induced pancreatitis. Our novel results demonstrate that TDPs exert protective effects against pathological inflammation and tissue damage in AP. These findings suggest that TDPs might be useful in the management of patients with severe AP.